Development of high voltage pulse generator using solid state devices / Abdul Shukor Jaffar and Syed Khanafiah Syed Abas - Jaffar, Abdul Shukor; Syed Abas, Syed Khanafiah (1993)
The development of the HIGH VOLTAGE PULSE GENERATOR USING SOLID STATE DEVICES, INCORPORATED WITH COCKROFT WALTON STACK.